Single-molecule analysis of G protein-coupled receptor stoichiometry: Approaches and limitations - Felce, J; Davis, S; Klenerman, D (Elsevier, 2017)
How G protein-coupled receptors (GPCRs) are organized at the cell surface remains highly contentious. Single-molecule (SM) imaging is starting to inform this debate as receptor behavior can now be visualized directly, without the need for interpreting ensemble data. The limited number of SM studies of GPCRs undertaken to date have strongly suggested that dimerization is at most transient, and that most receptors are monomeric at any given time. However, even SM data has its caveats and needs to be interpreted carefully. Here, we discuss the types of SM imaging strategies used to examine GPCR stoichiometry and consider some of these caveats. We also emphasize that attempts to resolve the debate ought to rely on orthogonal approaches to measuring receptor stoichiometry.